Teachers’ Perception on The New Policy Called Merdeka Belajar; A Page of Lesson Plan - Wierna Aulia, Reiga (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2021)
The Ministry of Education and Culture released a form letter in 2019 called Merdeka Belajar containing the policy of simplification of the RPP/Lesson Plan. Therein explained about the new format of lesson plan that only need to put or include 3 core components which are; Learning objectives, Learning activities and Assessment rather than putting all of the components from the usual lesson plan. Regarding to the new policy, this qualitative study aims to know teachers’ perception on it and collect their opinions toward the simplification of RPP/Lesson Plan using questionnaires as the instrument. The result showed that teachers agree that the 3 components are the most important components to be included in the lesson plan preparation. The result also showed that although few of them think additional attachmentsare still needed, while others think that it will be better to arrange and have such kind of lesson plan, which is simple but solid.